HUMAN-NATURE RELATIONSHIP IN SALIH'S 'A HANDFUL OF DATES' SHORT STORY AND LEE'S 'PERSIMMONS' POEM - Fakhrunnisa Fakhrunnisa (UIN Raden Mas Said Surakarta, 2020)
This study aims to examine human-nature relationships presented in the characters from the short story A Handful of Dates by Tayeb Salih and Persimmons by Li Young Lee.In analyzing the texts, this study usesKellertâ€™stypology of values on nature to examine the characters in revealing human-nature relationships.This study was conducted by: (1) analyzing the characters based on a typology of nine values of nature; (2) identifying the human-nature relationship reflected by characters; (3) drawing conclusions concerning with human-nature relationships found in both the text. This study finds out that the characters in both texts are utilitarian, moralistic, humanistic, ecologistical-scientific, symbolic, dominionistic, negativistic, and aesthetic. The characters who are moralistic, humanistic, and ecologistical-scientific perform positive human-nature relationship with nature and the characters who are utilitarian, dominionistic, and negativistic perform negative actions againts Â nature.